1975
DOI: 10.1056/nejm197510092931501
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Infection in Dentists

Abstract: To evaluate viral hepatitis as a hazard in general dentistry, we surveyed participants in an annual health-screening program at the 1972 American Dental Association session. Of 1245 practitioners, 0.9 per cent were positive for hepatitis B surface antigen, and 12.7 per cent were antibody positive. Of those who had had clinical hepatitis while studying or practicing dentistry, 43 per cent were seropositive. The frequency of evidence for prior infection with hepatitis B virus increased uniformly with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(30 citation statements)
references
References 25 publications
1
26
0
1
Order By: Relevance
“…Clinical research has found that the primary occupationally related route of blood‐borne pathogen transmission in dentistry is through percutaneous injury 2 . Research has indicated that dentists have a three‐fold greater risk than the general population of contracting hepatitis B virus 3 . In a retrospective study 4 of 310 dental practitioners who took part in the investigation, 56% of respondents reported at least one inoculation injury within the previous year.…”
mentioning
confidence: 99%
“…Clinical research has found that the primary occupationally related route of blood‐borne pathogen transmission in dentistry is through percutaneous injury 2 . Research has indicated that dentists have a three‐fold greater risk than the general population of contracting hepatitis B virus 3 . In a retrospective study 4 of 310 dental practitioners who took part in the investigation, 56% of respondents reported at least one inoculation injury within the previous year.…”
mentioning
confidence: 99%
“…4 With the emergence of the AIDS epidemic in the 1980s, even more stringent precautions became necessary to effectively protect health care workers and the public, leading to the recommendations by the U.S. Centers for Disease Control and Prevention (CDC) concerning the prevention of HIV transmission in health care settings and universal precaution guidelines. 4 With the emergence of the AIDS epidemic in the 1980s, even more stringent precautions became necessary to effectively protect health care workers and the public, leading to the recommendations by the U.S. Centers for Disease Control and Prevention (CDC) concerning the prevention of HIV transmission in health care settings and universal precaution guidelines.…”
mentioning
confidence: 99%
“…Other research-mitted in the same way as HBV, and far ers have found that perception of low HIV-less infectious, is a demand of pretreatment prevalence among patients is correlated to a antibody testing. The fact have a relatively high prevalence of antibod-that the dentists who answered in agreement ies to HBV (5,6). of mechanical barriers such as gloves has 'Several studies have shown that dentists been well proven for years (13).…”
Section: Discussionmentioning
confidence: 99%